2020
DOI: 10.21203/rs.3.rs-47586/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Alcohol Strength on Alcohol Consumption: Findings from A Randomised Controlled Cross-Over Pilot Trial.

Abstract: Background Reducing the alcohol content of drinks has the potential to reduce population level alcohol consumption. This pilot study aimed to (1) test the feasibility of a randomised controlled trial (RCT) to assess the effect of alcohol strength on alcohol consumption within licensed premises in the United Kingdom (UK); and (2) provide data to estimate key parameters for a RCT. MethodsA double-blind randomised controlled cross-over pilot trial was based within four licensed premises in the UK. Participants (n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A similar process could occur with alcoholic drink manufacturers, and reductions to energy content could be achieved through introducing new products 56 or reducing existing serving size and/or alcohol content by volume (ABV). As both reductions to alcoholic beverage serving sizes 57 and ABV 58 decrease alcohol consumption, industry reformulation as a result of energy labeling may be beneficial to public health.…”
Section: Discussionmentioning
confidence: 99%
“…A similar process could occur with alcoholic drink manufacturers, and reductions to energy content could be achieved through introducing new products 56 or reducing existing serving size and/or alcohol content by volume (ABV). As both reductions to alcoholic beverage serving sizes 57 and ABV 58 decrease alcohol consumption, industry reformulation as a result of energy labeling may be beneficial to public health.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published overview of the literature on production, consumption and impact of low and no-alcohol drinks [5], we found very little research on this topic coming from a public health perspective (e.g. on labelling [6][7][8] and marketing [9]) and almost no research focusing on whether low-and no-alcohol products can contribute to reduction in overall ethanol consumption, although at least one innovative trial attempting to answer this question with reduced alcohol beer is currently in progress [10], and another small study found that reduction in wine alcohol content did not lead to increase of wine consumed [11]. Thus at this point, it is too early to make conclusions about this approach as a public health measure aimed at reducing alcohol-related harm.…”
Section: Introductionmentioning
confidence: 99%
“…A similar process could occur with alcoholic drink manufacturers and reductions to energy content could be achieved through introducing new products 52 , or reducing existing serving size and/or alcohol content by volume (ABV). As both reductions to alcoholic beverage serving sizes 53 and ABV 54 decrease alcohol consumption, industry reformulation as a result of energy labelling may be beneficial to public health.…”
Section: Discussionmentioning
confidence: 99%